Models Don't Decompose That Way: A Holistic View of Idealized Models. (30th August 2017) - Rice, Collin
Abstract: Many (if not most) accounts of scientific modelling assume that models can be decomposed into the contributions made by their accurate and inaccurate parts. These accounts then argue that the inaccurate parts of the model can be justified by distorting only what is irrelevant. In this article, I argue that this decompositional strategy requires three assumptions that are not typically met by our best scientific models. In response, I propose an alternative view in which idealized models are characterized as holistically distorted representations that are justified by allowing for the application of various (mathematical) modelling techniques. 1 Introduction 2 The Decompositional Strategy 2.1 Mechanistic modelling and decomposition 2.2 Accounts of explanation that require decomposition 2.3 Accounts of idealization that require decomposition 2.4 Robustness analysis and decomposition 2.5 Scientific realism and decomposition 2.6 Three assumptions of the decompositional strategy 3 Against the Decompositional Strategy 3.1 Many scientific models don't decompose that way 3.2 Many idealizations distort difference-making features 4 An Alternative Approach: The Holistic Distortion View of Idealized Models 5 Conclusion